2015
DOI: 10.1155/2015/451049
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Identification and Control in Real-Time of a Robot Manipulator via Recurrent Wavelet First-Order Neural Network

Abstract: A decentralized recurrent wavelet first-order neural network (RWFONN) structure is presented. The use of a wavelet Morlet activation function allows proposing a neural structure in continuous time of a single layer and a single neuron in order to identify online in a series-parallel configuration, using the filtered error (FE) training algorithm, the dynamics behavior of each joint for a two-degree-of-freedom (DOF) vertical robot manipulator, whose parameters such as friction and inertia are unknown. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…For the application of the filtered error algorithm, this study begins under the assumption of an unknown system (3), which can be modeled (identified) by using an RWFONN structure (5). The synaptic weights are adjusted according to the following update law [23,24]…”
Section: Filtered Error Training Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…For the application of the filtered error algorithm, this study begins under the assumption of an unknown system (3), which can be modeled (identified) by using an RWFONN structure (5). The synaptic weights are adjusted according to the following update law [23,24]…”
Section: Filtered Error Training Algorithmmentioning
confidence: 99%
“…This latter will guarantee that the tracking errors be steered to zero in finite time. From Equation (24), selecting the sliding surface s = x 2 arises the system given by [29] ṡ =a pinv 1…”
Section: Pmsm Parameters Valuementioning
confidence: 99%
“…Compared with other wavelets such as Haar wavelet, Mexican Hat wavelet and Daubechies wavelet, Morlet wavelet has better local characteristics in the time domain and frequency domain, which is adopted as the activation function of WNN. [17][18] WNN combines the structure model of neural network with the multi-resolution and multi-scale analysis of signals effectively, so it has better performance in signal direction selection. 19 The introduction of WNN in servo control system has attracted wide attention and research.…”
Section: Introductionmentioning
confidence: 99%
“…Wavelet Neural Networks (WNN) are complex machine learning algorithms that use wavelet analysis and neural networks to generate prediction and control models. WNNs have been applied before in several areas, including time-series prediction and control [ 13 , 14 ]. Evolutionary Wavelet Neural Networks (EWNN) are a recently proposed method for training WNNs and have been used to generate models for breast cancer and Parkinson’s disease classification [ 15 ].…”
Section: Introductionmentioning
confidence: 99%